Cardamine panatohea (Brassicaceae), a new, threatened, alpine species from New Zealand - Heenan, Peter B.; de Lange, Peter J. (Phytotaxa, 2018)
A new species, Cardamine panatohea, is named and described from the central North Island, New Zealand. Cardamine panatohea is characterised by a suite of characters that are unique among the New Zealand Cardamine species, including decumbent inflorescences and rosettes in the axils of the lateral inflorescence branches. Cardamine panatohea is known from two localities on Mt Ruapehu where it occurs in alpine flushes. It is assigned a New Zealand conservation status of Threatened, Nationally Critical.